2010
DOI: 10.1590/s1980-57642010dn40200008
|View full text |Cite
|
Sign up to set email alerts
|

Mini- Mental State Examination among lower educationl levels and illiterates: transcultural evaluation

Abstract: Cognitive performance among illiterates and low educational levels is poorer than that observed in individuals with greater schooling. This difference can be a confounding factor in reaching an accurate diagnosis of cognitive impairment. In addition, there is great heterogeneity in performance among illiterates, probably due to different environmental demands and sociocultural backgrounds. Many reports have described the influence of education on neuropsychological measures and screening tests such as the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
(23 reference statements)
0
22
0
4
Order By: Relevance
“… 17 Populations in the same country with the same spoken language were subject to cultural influences, as demonstrated by the authors with the Mini-Mental State examination, which revealed a difference between two samples from urban and rural areas. 18 …”
Section: Epidemiologymentioning
confidence: 99%
“… 17 Populations in the same country with the same spoken language were subject to cultural influences, as demonstrated by the authors with the Mini-Mental State examination, which revealed a difference between two samples from urban and rural areas. 18 …”
Section: Epidemiologymentioning
confidence: 99%
“…Brucki and Nitrini observed a significant difference in MMSE scores between two different samples (from São Paulo and that of a rural sample from the Amazonian region). 15 Moreover, number of years of schooling completed is inaccurate because some people continue their education informally. It is not uncommon to encounter individuals with one or two years of formal education, but who are able to comprehend, make inferences or discuss complex subject matter.…”
mentioning
confidence: 99%
“…Variables concerning the present environment, life history, individual action and subjective assessments are thought to provide multiple old-age realities, within objective and subjective health and physical, social and psychological well-being conditions. 4 , 5 , 12 This leads us to consider that our study sample might have been influenced by a cohort effect whereby this group of old-older adults may have different variables compared to the middle-old.…”
Section: Discussionmentioning
confidence: 99%